Sol–gel combustion synthesis and study the high frequency dielectric properties of copper ferrite nanoparticles - Samikannu, Kanagesan; Ahmad, Ahmad Fahad; Ismail, Ismayadi; Aspanut, Zarina; Abd Majid, Wan Haliza (Springer, 2023)
In recent years, the spinel structures of the ferrite compounds are known for their remarkable versatile applications. In this work, CuFe2O4 nanoparticles were successfully synthesized by sol–gel combustion technique. The properties of the samples were analyzed by Fourier Transform Infrared Spectroscopy, X-Ray Diffraction, Transmission Electron Microscope, Vibrating Sample Magnetometer. The complex permittivity (ε) and the complex permeability (μ) of the Cu-ferrites have been measured using the waveguide technique at frequency range 8–12 GHz and 12–18 GHz which represent X-band and Ku-band, respectively. It is found to increase the dielectric and magnetic properties with thicknesses increases but is almost constant with the frequency of both frequencies. The results illustrate, the potentiality used this nanomaterial for applications like suppression of electromagnetic interference in microwave circuits. The spinel CuFe2O4 nanoparticles showed sphere-like spherical particles with an average size of about 30 nm.